Detection Of Fire-Prone Areas In Attica Region Integrating Urban And Transport Aspect - Efthymia Kourmpa; Stefanos Tsigdinos (Geography, Environment, Sustainability)
In Mediterranean climate areas, wildfires are one of the most critical problems bringing about several negative impacts (loss of human life, infrastructure damages, landscape transformation, natural environment deterioration, etc.). Fires pose great dangers not only for rural areas, but also for suburban or even urban areas. The aim of the research is to detect areas vulnerable to wildfire in Attica Region and then to examine the critical factors affecting the risk degree in macro and microscale. In the first step we examine the wider study area, which is close to vulnerable areas in a zone at least 1km wide. This examination includes the factor of vegetation along with other factors such as road network, aspect, slope etc, aiming to detect the exact area vulnerable to fire. The second step focuses on a vulnerable study area individually, for identifying and measuring the factors that affect the risk degree in microscale. The most notable factors are: a) population density, b) connectivity of the road network, c) geometric features of the streets, c) location of fire stations and police departments, d) existence of open spaces, e) parking conditions and f ) existence of vulnerable facilities. The wider study area (macroscale) is the Regional Unit of Eastern Attica and the main study area (microscale) is the settlement of Saronida. The findings indicate that several rural and peri-urban areas inEastern Atticaare vulnerable to wildfire. Particularly, crucial issues regarding microscale are the low roadway width values and the inadequate connectivity of the network structure.